TUBERCULOUS MASTITIS - Ariani Vitriasari, Ni Wayan; Tusta Adiputra, Putu Anda; Maliawan, Sri (E-Jurnal Medika Udayana; vol 2 no2 (2013):e-jurnal medika udayana)
Tuberculous mastitis is a condition marked pathologyly with involvement extensively mamma lobules with epitheloid granuloma with various degree of caseation, what consist of Langhan's cells giant, cells of epiteloid, mononuclear cell infiltrate, with surrounding fibrosis, and with micro forming of abscess, which because of infection of Mycobacterium tuberculosis. Tuberculous mastitis happened more often at developing countries than developed countries, and especially happened at reproductive woman. The risk factors of this disease are lactation, multiparity, trauma, history of previous suppurative mastitis, and acquired immune deficiency syndrome (AIDS). Diagnose of tuberculous mastitis can be confirm by anamnesis, physical examination, and also some additional diagnostic test such as mammography, ultrasonography, computerized tomography scan (CT scan), scintimammography, magnetic resonance imaging (MRI), 3D magnetic resonance mammography, Gd-DTPA enhanced dynamic MRI, cytology, histopatology, culture, polymerase chain reaction (PCR), X-Ray, dan Mantoux skin test. Anti-tuberculous therapy forms the mainstay of treatment and conservative surgery is restricted to selected cases.
Keywords: Tuberculous mastitis, Mycobacterium tuberculosis